Transformation of 2-(acetamido)-3-(4-chlorophenyl)acrylohydrazide into 1-arylideneamino-4-(4-chlorobenzylidene)-2-methyl-1H-imidazolin-5(4H)-ones and 4-aryl-1-[2-(acetamido)-3-(4-chlorophenyl) acryloyl]thiosemicarbazides - Cong, Nguyen Tien; Anh Luan, Truong Ngoc (Vietnam Journal of Chemistry, 2016)
Six 1-arylideneamino-4-(4-chlorobenzylidene)-2-methyl-1H-imidazolin-5(4H)-one compounds and two 4-aryl-1-[2-(acetamido)-3-(4-chlorophenyl)acryloyl]thiosemicarbazide compounds were synthesized by reaction of aromatic aldehydes or reaction of aryl isothiocyanates, respectively with 2-(acetamido)-3-(4-chlorophenyl)acrylohydrazide which was prepared starting from 4-chlorobenzaldehyde and acetylglycine via 4-(4-chlorobenzylidene)-2-methyloxazol-5(4H)-one. The structures of the synthesized compounds were determined by IR, NMR and mass spectral data. Keywords. 2-(acetamido)-3-(4-chlorophenyl)acrylohydrazide, imidazolin-5(4H)-one, thiosemicarbazide.